INFLUENCE OF ULTRA-PROCESSED FOOD CONSUMPTION ON THE MUSCLE STRENGTH OF WORKERS: A CROSS-SECTIONAL STUDY IN THE SÃO PATRÍCIO VALLEY, GOIÁS - Costa, Milka Barbosa; Cordeiro, Lavínia Leal; Oliveira, Isabela Fernanda Rodrigues de; Jesus, José Igor Ferreira Santos; Nogueira, Suelen Marçal; Silva, Priscilla Rayanne e; Noll, Matias (CIPEEX, 2025)
Introduction: The consumption of ultra-processed foods has grown among Brazilians, usually associated with negative health effects. However, in work contexts, where there is greater physical demand and energy expenditure, this relationship may be more complex. Assessing how this dietary pattern is associated with muscular strength in workers can contribute to more contextualized health promotion strategies in the occupational environment. Objective: to evaluate the association between regular consumption of ultra-processed foods, such as sweets, soft drinks and fast food, and the levels of manual, scapular and lumbar muscle strength in workers in the interior of Goiás. Methods: This is a cross-sectional study with a quantitative approach involving workers of both sexes, aged 18 years or older, employed by public and private companies. Food consumption was assessed based on blocks of the National School Health Survey Qquestionnaire, considering as regular consumption whem it was equal to or greater than 5 days on the last week. Muscle strength was classified as low or high based on the median, and measured using manual dynamometry (right and left hand), scapular and lumbar, respecting the collection protocols and considering the highest value among 3 attempts. Data analysis was performed using SPSS software, version 23.0. To verify the association between the variables, Poisson Regression with robust variance was used through the Generalized Linear Model (p=0.05). Results: 804 workers participated in the study, 512 women (63.7%) and 292 men (36.3%). A significant association was observed between regular consumption of sweets and a lower prevalence of low lumbar strength among women, only 39.0% of those who consumed sweets regularly had low lumbar strength, compared with 53.4% of those who consumed sweets irregularly (p = 0.011). Similarly, regular consumption of soft drinks was also associated with a lower risk of low lumbar strength in both sexes. Among women, only 31.4% of those who consumed soft drinks regularly had low lumbar strength, in contrast to 53.1% who consumed them irregularly (p = 0.004). Among men, the percentages were 38.3% and 54.7%, respectively (p = 0.041). No significant associations were observed between fast food consumption and muscle strength levels or between the consumption of the analyzed foods and hand or scapular strength, regardless of gender. Conclusion: It is concluded that the regular consumption of sweets and soft drinks was associated with a lower risk of low lumbar strength in workers, possibly related to the greater caloric and energy intake. These findings reinforce the need to investigate nutritional impacts in the occupational context in more depth, considering not only the quality of food, but also the energy demands related to physical work and the maintenance of muscle strength.